Spaceborne Synthetic Aperture Radar (SAR) Systems: State of the Art and Future Developments - Moreira, Alberto; Krieger, Gerhard (European Microwave Conference, 2003)
This paper first summarizes the state of the art in spaceborne SAR systems and applicatiøn the second part of this paper gives an overview of new concepts, techniques and technologies for future SAR systems, allowing an increase of flexibility the SAR operation mode as well as a reduction in the overall system costs. Several innovative concepts and technologies as bi and multistatic configurations, parasitic SAR, sparse aperture systems and digital beamforming will play an Important role forfuture spaceborne SAR constellations. © 2003 EUMA.
DLR Import::2019-04-03